Kegiatan Pengabdian Masyarakat dalam Rangka Skrining Kadar Vitamin D Sebagai Penyebab Insomnia pada Geriatri - Biromo, Anastasia Ratnawati; Santoso, Alexander Halim; Destra, Edwin; Gunaid, Farell Christian; Pratomo, Farhan; Lumintang, Valentino Gilbert (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Vitamin D is an essential steroid hormone that plays a role in calcium and phosphorus regulation and has the potential to affect sleep quality. Vitamin D deficiency in the elderly often occurs due to minimal exposure to sunlight and age-related physiological changes, which contribute to the high incidence of sleep disorders, including insomnia. This community service activity aims to screen vitamin D levels in the elderly as a cause of insomnia through the Plan-Do-Check-Act (PDCA) approach. The activity was carried out at Panti Bina Bhakti, South Tangerang, involving 93 elderly participants aged > 65 years. The results showed that the average vitamin D levels among the age groups 61-70 years, 71-80 years, 81-90 years, and 91-100 years were 7.6 mg/dl, 7.2 mg/dl, 7.6 mg/dl, and 13.9 mg/dl, respectively. Interventions through vitamin D supplementation, sunlight exposure, and education in the form of sleep hygiene are effective in improving the health and sleep quality of the elderly.